2018
DOI: 10.1016/j.jtho.2018.06.007
|View full text |Cite
|
Sign up to set email alerts
|

Histology, Tumor Volume, and Radiation Dose Predict Outcomes in NSCLC Patients After Stereotactic Ablative Radiotherapy

Abstract: In the absence of level I data, GTV and histology should be considered to personalize radiation dose for stereotactic ablative body radiotherapy. We suggest lower prescription doses (i.e., 12 Gy × 4 or 10 G × 5) should be avoided for squamous cell carcinomas if normal tissue tolerances are met.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
23
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 30 publications
(41 reference statements)
4
23
1
Order By: Relevance
“…Regarding the former, we posit that our high institutional prescription doses (with median BED 10 of 112.5 Gy for the study population) may mitigate the adverse prognostic effect of squamous cell carcinoma histology. 39 This hypothesis is corroborated by prior studies by Hörner-Rieber et al 40 and Woody et al 41 both of which evaluated escalating prescription doses. As for the latter, we did find pre-SABR SUV max to be significantly associated with distant failure (similar to a previous report 38 ), although it was not identified as a predictor for TTP in general.…”
Section: Discussionsupporting
confidence: 58%
“…Regarding the former, we posit that our high institutional prescription doses (with median BED 10 of 112.5 Gy for the study population) may mitigate the adverse prognostic effect of squamous cell carcinoma histology. 39 This hypothesis is corroborated by prior studies by Hörner-Rieber et al 40 and Woody et al 41 both of which evaluated escalating prescription doses. As for the latter, we did find pre-SABR SUV max to be significantly associated with distant failure (similar to a previous report 38 ), although it was not identified as a predictor for TTP in general.…”
Section: Discussionsupporting
confidence: 58%
“…Patients were excluded if they had evidence of systemic spread of lung cancer at the time of SBRT. Radiation planning and treatment details have been previously reported [15]. Prescriptions typically were to the 80% isodose line, and the prescription typically covered at least 95% of the PTV.…”
Section: Study Populationmentioning
confidence: 99%
“…Prior studies have shown that SBRT may be associated with unacceptable toxicity for tumors greater than 5 cm [2], [3]. Also, large tumors may be near surrounding OARs, which can make planning difficult [4], [5].…”
Section: Introductionmentioning
confidence: 99%